The mitochondrial gene-CMPK2 functions as a rheostat for macrophage homeostasis - Arumugam, Prabhakar; Chauhan, Meghna; Rajeev, Thejaswitha; Chakraborty, Rahul; Bisht, Kanika; Madan, Mahima; Shankaran, Deepthi; Ramalingam, Sivaprakash; Gandotra, Sheetal; Rao, Vivek (Frontiers in Immunology, 2022)
In addition to their role in cellular energy production, mitochondria are increasingly recognized as regulators of the innate immune response of phagocytes. Here, we demonstrate that altering expression levels of the mitochondria associated enzyme, cytidine monophosphate kinase 2 (CMPK2), disrupts mitochondrial physiology and significantly de-regulates the resting immune homeostasis of macrophages. Both CMPK2 silenced as well as constitutively over expressing macrophage lines portray mitochondrial stress with marked depolarization of their membrane potential, enhanced ROS and disturbed architecture culminating in the enhanced expression of the pro-inflammatory genes- IL1β, TNFα and IL8. Interestingly, the long-term modulation of CMPK2 expression resulted in an increased glycolytic flux of macrophages akin to the altered physiological state of activated M1 macrophages. While infection induced inflammation for restricting pathogens is regulated, our observation of a total dysregulation of basal inflammation by bidirectional alteration of CMPK2 expression, only highlights a critical role of this gene in mitochondria mediated control of inflammation.